2022
DOI: 10.1021/acsanm.2c02985
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation and Encapsulation of In Situ Grown Black Phosphorus within Ti3C2Tx MXene Sheets for Energy Storage

Abstract: An innovative yet simple approach for the in situ growth of black phosphorus (BP) over MXene sheets has been carried out by a facile and simple hydrothermal treatment. Basically, a dual strategy is adopted to expand MXene interlayer spacing by in situ intercalation of BP along with encapsulation with an antioxidant agent to prevent oxidation at elevated temperatures. Detailed nucleation and growth mechanisms are explained by optimizing the ratio of BP in MXene–BP hybrid material supported by XRD, FE-SEM, FT-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Figure 10 shows that the BPNS represented the minimum arc radius, indicating the low charge transfer resistance in BPNS. In contrast, the arc radius of the Bi 2 MoO 6 was the largest among these samples, demonstrating that the charge In the P 2p spectra of BPNS, the binding energy of P 2p 1/2 , P 2p 3/2 , and P-O was 131.03 eV, 130.177 eV and 134.695 eV, respectively [53]. There was no significant P-O signal in the P 2p spectrum of the composite catalyst, indicating that the stability of BPNS is greatly enhanced and it is more difficult to oxidize after coupling with Bi 2 MoO 6 .…”
Section: Resultsmentioning
confidence: 91%
“…Figure 10 shows that the BPNS represented the minimum arc radius, indicating the low charge transfer resistance in BPNS. In contrast, the arc radius of the Bi 2 MoO 6 was the largest among these samples, demonstrating that the charge In the P 2p spectra of BPNS, the binding energy of P 2p 1/2 , P 2p 3/2 , and P-O was 131.03 eV, 130.177 eV and 134.695 eV, respectively [53]. There was no significant P-O signal in the P 2p spectrum of the composite catalyst, indicating that the stability of BPNS is greatly enhanced and it is more difficult to oxidize after coupling with Bi 2 MoO 6 .…”
Section: Resultsmentioning
confidence: 91%
“…Mo borides and 2D MBenes have gained interest in energy storage applications due to their several unusual physicochemical properties with key advantages such as large surface area, active edge sites, high mechanical properties, flexibility, etc. [20,44,[58][59][60][61][62] 4.1.1. Battery Theoretical predictions showed that molybdenum borides and MBenes have inherent mechanical anisotropy and metallic properties, low diffusion potential, and low open circuit voltage.…”
Section: Energy Storage Devicesmentioning
confidence: 99%
“…Mo borides and 2D MBenes have gained interest in energy storage applications due to their several unusual physicochemical properties with key advantages such as large surface area, active edge sites, high mechanical properties, flexibility, etc. [ 20 , 44 , 58 , 59 , 60 , 61 , 62 ]…”
Section: Applications Of Molybdenum Borides and Mbenesmentioning
confidence: 99%
“…Sharma et al [ 221 ] developed a simple method to combine the benefits of incorporating black phosphorus (BP) nanoparticles into Ti 3 C 2 T x MXene sheets and the protective effect of L-ascorbic acid encapsulation of Ti 3 C 2 T x -BP nanostructures against oxidation, even under high-temperature conditions, during hydrothermal reactions. The intercalation of BP and the subsequent passivation with antioxidants helped prevent oxidation at high temperatures above 100 °C during hydrothermal processes.…”
Section: Binary Mxene-based Supercapacitorsmentioning
confidence: 99%